Telephonic Nurse Guidance for Colonoscopy: A Clinical Trial - Diniz, Tatiane Santa Rosa [UNESP]; Fusco, Suzimar de Fátima Benato [UNESP]; Oliveira, Maria Elizandre Camilo de [UNESP]; Nunes, Hélio Rubens de Carvalho [UNESP]; Avila, Marla Andréia Garcia de [UNESP] (SAGE Publications, 2021)
This study aims to analyze the effectiveness of nurse-conducted telephone guidance for bowel preparation before a colonoscopy after patients have received routine recommendations. A randomized, controlled, colonoscopist-blinded clinical trial was conducted at a Brazilian teaching hospital. Participants included patients aged ≥ 18, who were available via telephone (the intervention group was given guidance over telephone). Of the 109 total participants, 55 were placed into the intervention group (IG) and 54 into the control group (CG). Outcomes included Boston Bowel Preparation Scale (BBPS) scores, adenoma detection, and cecal intubation. Total BBPS scores showed a statistically significant reduction for the IG when compared to the CG (p <.001) (all colon segments were evaluated thus). Cecal intubation occurred in all exams for those in the IG (p =.027). No significant differences were found regarding adenoma detection. The examined educational intervention was an effective strategy for reeducating patients about bowel preparation.
Keywords: bowel preparation; colonoscopy; health education; nursing; randomized controlled trial